Electrocatalytic response of dopamine at a carbon paste electrode modified with ferrocene - Ali Kamyabi, Mohammad (Array, 2009)
Summary: Carbon paste electrodes modified by ferrocene (Fc) were used for electrocatalytic oxidation and determination of dopamine. The modified carbon paste electrode shows excellent electrocatalytic activity toward the oxidation of dopamine (DA) in a phosphate buffer solution (pH = 6.0). A anodic oxidation of DA (in pH = 6.0) at the Fc-modified carbon paste electrode occurred at low overpotential (0.18 V vs. Ag ‌ AgCl), and treatment of the voltammetric data showed that it was a purely diffusion-controlled reaction with the involvement of one electron in the rate-determining step. The mechanism for the interaction of DA at the Fc modified CPE is proposed. The rate constant k', transfer coefficient α for the catalytic reaction and the diffusion coefficient of DA in the solution, D, were found to be 6.92×10–2 cm s–1, 0.71 and 1.41×10−5 cm2 s−1, respectively. The interference of ascorbic acid was investigated and greatly reduced using sodium tetraphenylborate incorporated modified carbon paste electrodes